Effect Of Lean Tools and Techniques for Improving Manufacturing Performance in M/S. Sri Devi Foundry Scenario in Ranipet – Tamil Nadu: A Case Study - K.Gurusami, Dr. (International Journal of Engineering and Technology, 2018)
The intention of this study is to examine the implementation of lean manufacturing tools and techniques in the M/s. Sri Devi Foundry at Ranipet.  A questionnaire survey was used to discover 14 main input areas of lean manufacturing namely, inventory, material handling, scheduling, equipment, employees,, quality, layout, suppliers, customers, safety and ergonomics, product design, work-processes, management and culture, and tools and techniques. The target respondents were asked to rate the degree of implementation for each of these areas. The average mean score of each area was computed and some statistical analyses were then achieved.  In addition, the survey also studied various subjects associated with lean manufacturing such as its understanding among the respondent companies, its benefits and obstacles, the tools and techniques used, etc. The survey results show that many foundries are dedicated to employ lean manufacturing. Commonly, most of them are “moderate-to-extensive” implementers.  All the 14 main areas investigated serve as a useful guide to organizations when they are adopting lean manufacturing. In essence, this is perhaps the first learning that investigates the actual implementation of lean manufacturing in foundry production.
Keywords: Lean manufacturing tools and techniques; foundry; Tamil Nadu.